2020
DOI: 10.3846/ijspm.2020.13676
|View full text |Cite
|
Sign up to set email alerts
|

Bim Adoption in the Aec/Fm Industry – The Case for Issuing Building Permits

Abstract: BIM adoption is a complex process and relatively little information exists on the BIM adoption processes of public authorities. This research aims to address this gap by examining how a contemporary public authority is approaching BIM adoption for their building permitting process. Firstly, a systematic literature review was carried out to understand extant descriptions of BIM adoption processes and the factors affecting adoption success. This resulted in the derivation of a generic BIM adoption process and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Publications within the Generic category include works such as Ullah et al [16], who describe how public authorities are approaching BIM adoption, underlining planning strategies and steps of implementation. In addition, Kim et al [17] explore the impacts of the lack of data in public organisations; Abdirad and Dossick [43] draw a map for collecting data through BIM in the management phase of two large public owners in the U.S; a similar approach, discussed from the point of view of public actors in general, is given by Brunet et al [45], who define a methodological approach for taking advantages of BIM for asset management purposes.…”
Section: Building Typologymentioning
confidence: 99%
See 1 more Smart Citation
“…Publications within the Generic category include works such as Ullah et al [16], who describe how public authorities are approaching BIM adoption, underlining planning strategies and steps of implementation. In addition, Kim et al [17] explore the impacts of the lack of data in public organisations; Abdirad and Dossick [43] draw a map for collecting data through BIM in the management phase of two large public owners in the U.S; a similar approach, discussed from the point of view of public actors in general, is given by Brunet et al [45], who define a methodological approach for taking advantages of BIM for asset management purposes.…”
Section: Building Typologymentioning
confidence: 99%
“…Previous studies in this area have focused mainly on applying building information modelling in the FM field in general [16][17][18], approaching the subject from a practical point of view [19][20][21] and without an in-depth analysis of the public involvement. On the other hand, several researchers investigated BIM-FM adoption, considering both the public and private sectors and discussing the overall implementation status [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…This study found that the “support from top management” and “functionality” of BIM tools are the two most significant factors for BIM adoption among total 58 CSFs [ 82 ]. More recently, Ullah et al [ 83 ] also implemented the Technology Organization and Environment framework to investigate and classify the factors that affect BIM adoption in a contemporary public authority from the literature. However, scant research has been provided to characterize the critical factors of BIM adoption behavior from the perspective of the Theory of Planned Behavior (TPB).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical data on the difference between digital models and construction takeoffs are hard to find and this might be an interesting development for future studies. The spread of BIM is leading to a new digitalized method to archive and process construction permits in cities (Chognard et al., 2018; Noardo et al., 2020; Ullah et al., 2020), including the creation of material passports (Honic et al., 2019). The integration of 3D building models into the administration of the urban form allows for a much greater understanding of the location of material stocks in the context of urban mining (Ghisellini & Ulgiati, 2020; Koutamanis et al., 2018).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%